Covid-19 pandemic effects on food safety - Multi-country survey study. (April 2021) - Djekic, Ilija; Nikolić, Aleksandra; Uzunović, Mirza; Marijke, Aluwé; Liu, Aijun; Han, Jiqin; Brnčić, Mladen; Knežević, Nada; Papademas, Photis; Lemoniati, Katerina; Witte, Franziska; Terjung, Nino; et al.
Abstract: This study provides an important insight into the response of food safety systems during the first months of the pandemic, elevating the perspective of preventing Covid-19 within conventional food safety management systems. A multi-country survey was conducted in 16 countries involving 825 food companies. Based on the results of the survey, it is obvious that the level of maturity of a food safety system in place is the main trigger in classifying companies and their responses to the pandemic challenge. Staff awareness and hygiene are the two most important attributes in combating Covid-19, opposed to temperature checking of workers in food establishment and health protocols from the World Health Organization, recognized as attributes with limited salience and importance. Companies confirmed implementation of more restrictive hygiene procedures during the pandemic and the need for purchasing more additional personal protective equipment. Retailers were identified as the food supply chain link mostly affected by the pandemic opposed to food storage facilities ranked as least affected. During this challenging period, all companies declared that food safety has not been compromised at any moment. It is important to note that less than a half of the food companies had documented any emergency plans associated with pandemics and health issues in place. Highlights: 825 food companies from 16 countries were included in this multi-country study. Maturity of a food safety system triggers the response to the Covid-19 pandemic. Staff awareness and hygiene are most important attributes combating Covid-19. Retailers are the food supply chain link mostly affected by the Covid-19 pandemic. Less than a half of companies have any emergency plans associated with pandemics.